Potential of Kesambi Active Compound (Schleichera oleosa) as Antagonist G-Protein Estrogen Receptor 1 (GPER1) by In Silico - Radita Intan Aisyah Pratiwi; Widyarti, Sri; Sumitro, Sutiman Bambang (Graduate School, Universitas Brawijaya, 2023)
Tamoxifen is a treatment for breast cancer patients which can cause side effects of endometrial cancer because it acts as a GPER1 agonist. Active compounds from Schleichera oleosa are known to have anticancer potential, such as schleicheol and schleicherastatin, especially their ability to prevent cell proliferation. This research conducted an in silico study to determine the potential of the active compound from S. Oleosa as a GPER1 inhibitor. In silico studies include molecular docking and molecular dynamics. The data obtained are binding affinity values, potential energy, RMSD, RMSF, and conformational changes. Active compound candidates with the lowest binding affinity were selected, namely Schleicheol 1 (SCL1), Lupeol (LU), Lupeol acetate (LA), Betulinic acid (BA), and Schleicherastatin 3 (SCR3) with an order of score -8.6, - 8.5, -8.4, -8.4 and -8.4 kcal.mol-1. When complexed with GPER1-Estradiol and GPER1-Tamoxifen, the lowest binding affinity was LU (-8.6 and -8.7 kcal.mol-1). LU binds to the same amino acid as Estradiol and Tamoxifen, namely Leu:271. Based on molecular dynamics, RMSD All (receptor complex) ranged from 3,723 to 5,098 Å, above the normal limit of 3 Å. However, RMSD All shows stability starting from 1.5 ns so that the resulting data can be used. The RMSF value showed higher fluctuations than Tamoxifen at the same binding site as Tamoxifen, including SCL1-T, LU-T, LA-T, and BA-T, which can interfere with the function of the GPER1 receptor. LU, LA, BA, SCL1-T LU-T, and LA-T with GPER1 produce the same structural changes as G15 as GPER1 antagonists. The active compound, especially lupeol, which has the lowest binding affinity, is predicted to have the potential to inhibit GPER1 in silico so that it can be proposed for further testing. Keywords: Endometrial Cancer, GPER1, Schleichera oleosa, Tamoxifen.